2013
DOI: 10.1039/c2tc00169a
|View full text |Cite
|
Sign up to set email alerts
|

Electro-optical properties of the nematic phase in V-shaped molecules with a 2,3-naphthalene central unit

Abstract: So far there is little understanding of the physicochemical properties of the nematic phase of V-shaped bent-core liquid crystalline (VBLC) molecules. We have synthesized VBLC molecules based on a 2,3naphthalene central unit, varying the carbon number of the flexible alkyl chains (n ¼ 2, 6 or 12) to extend the nematic range. We examined the polar and biaxial properties of the nematic phases for two homologous molecules with n ¼ 6 and 12.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Such materials are referred to acute angle mesogens, U-shaped, and/or V-shaped liquid crystals, respectively. The 1,2-disubstituted naphthalene-derived bent-shaped materials exhibited conventional SmA phases and the same was for naphthalene-2,3-diol derivatives, where SmA phase [23,24,28] and N-SmA phase sequence [27,29,30] were identified, suggesting that molecules in this phases are free to rotate around the axis of symmetry. More interesting results have been reported in the series of naphthalene-1,7-diol derivatives: the crystalline B 4 phase was identified in the PIMB-derivatives with a terminal alkoxy tail [24,34,37].…”
Section: Introductionmentioning
confidence: 60%
See 2 more Smart Citations
“…Such materials are referred to acute angle mesogens, U-shaped, and/or V-shaped liquid crystals, respectively. The 1,2-disubstituted naphthalene-derived bent-shaped materials exhibited conventional SmA phases and the same was for naphthalene-2,3-diol derivatives, where SmA phase [23,24,28] and N-SmA phase sequence [27,29,30] were identified, suggesting that molecules in this phases are free to rotate around the axis of symmetry. More interesting results have been reported in the series of naphthalene-1,7-diol derivatives: the crystalline B 4 phase was identified in the PIMB-derivatives with a terminal alkoxy tail [24,34,37].…”
Section: Introductionmentioning
confidence: 60%
“…The previously reported naphthalenediol-based 2,3-disubstituted materials exhibited a nematic and SmA phase [23,28,30]; however, the material VIIc was crystalline only. Finally, introduction of the side arms to position 1,7 of the naphthalene ring resulted, both in the naphthalenediol-based compounds [23,26] and in the studied compound of IXc, in the loss of mesomorphic properties or formation of higher organised phases.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…[8][9][10] Matsuzaki et al [11,12] were the first to synthesise V-shaped molecules of about 60°based on 1,2-phenylene and 2,3-naphthalene central core, which only show conventional SmA and Nematic phase. Choi [13,14] and Ros et al [15] have also reported some V-shaped molecules based on the 2,3-naphthalene central unit with ester type side wings, but no B phase appears for these acute-angle liquid crystal materials. In general, the introduction of obtuse angle bent-core had been thought to be essential to form the previously mentioned switchable B phases.…”
Section: Introductionmentioning
confidence: 92%